Metabolism-linked methylotaxis sensors responsible for plant colonization in Methylobacterium aquaticum strain 22A - Tani, Akio; Masuda, Sachiko; Fujitani, Yoshiko; Iga, Toshiki; Haruna, Yuuki; Kikuchi, Shiho; Shuaile, Wang; Lv, Haoxin; Katayama, Shiori; Yurimoto, Hiroya; Sakai, Yasuyoshi; Kato, Junichi (Frontiers in Microbiology, 2023)
Motile bacteria take a competitive advantage in colonization of plant surfaces to establish beneficial associations that eventually support plant health. Plant exudates serve not only as primary growth substrates for bacteria but also as bacterial chemotaxis attractants. A number of plant-derived compounds and corresponding chemotaxis sensors have been documented, however, the sensors for methanol, one of the major volatile compounds released by plants, have not been identified. Methylobacterium species are ubiquitous plant surface-symbiotic, methylotrophic bacteria. A plant-growth promoting bacterium, M. aquaticum strain 22A exhibits chemotaxis toward methanol (methylotaxis). Its genome encodes 52 methyl-accepting chemotaxis proteins (MCPs), among which we identified three MCPs (methylotaxis proteins, MtpA, MtpB, and MtpC) responsible for methylotaxis. The triple gene mutant of the MCPs exhibited no methylotaxis, slower gathering to plant tissues, and less efficient colonization on plants than the wild type, suggesting that the methylotaxis mediates initiation of plant-Methylobacterium symbiosis and engages in proliferation on plants. To examine how these MCPs are operating methylotaxis, we generated multiple gene knockouts of the MCPs, and Ca2+-dependent MxaFI and lanthanide (Ln3+)-dependent XoxF methanol dehydrogenases (MDHs), whose expression is regulated by the presence of Ln3+. MtpA was found to be a cytosolic sensor that conducts formaldehyde taxis (formtaxis), as well as methylotaxis when MDHs generate formaldehyde. MtpB contained a dCache domain and exhibited differential cellular localization in response to La3+. MtpB expression was induced by La3+, and its activity required XoxF1. MtpC exhibited typical cell pole localization, required MxaFI activity, and was regulated under MxbDM that is also required for MxaF expression. Strain 22A methylotaxis is realized by three independent MCPs, two of which monitor methanol oxidation by Ln3+-regulated MDHs, and one of which monitors the common methanol oxidation product, formaldehyde. We propose that methanol metabolism-linked chemotaxis is the key factor for the efficient colonization of Methylobacterium on plants.